Biomimetic growth and substrate dependent mechanical properties of bone like apatite nucleated on Ti and magnetron sputtered TiO2 nanostructure. (11th March 2016) - Sarma, Bimal K; Das, Apurba; Barman, Pintu; Pal, Arup R
Abstract: This report presents findings on biomimetic growth of hydroxyapatite (HAp) nanocrystals on Ti and sputtered TiO2 substrates. The possibility of TiO2 nanostructure as candidate materials for future biomedical applications has been explored through the comparison of microstructural and mechanical properties of bone like apatite grown on Ti and nano-TiO2 surfaces. Raman spectroscopy and x-ray diffraction studies reveal formation of carbonate apatite with apparent domain size in the nanoscale range. A better interaction at the nano-TiO2 /nano-HAp interface due to higher interfacial area could promote the growth of bone like apatite. The crystal phases, crystallinity, and surface morphology of nano-TiO2 are considered as parameters to understand the nucleation and growth of apatite with different mechanical properties at the nanoscale. The methodology of x-ray line profile analysis encompasses deconvolution of merged peaks by preserving broadening due to nanosized HAp aggregates. The Young's modulus of bone like apatite exhibits crystallographic directional dependence which suggests the presence of elastic anisotropy in bone like apatite. The lattice contraction in the c -direction is associated with the degree of carbonate substitution in the apatite lattice. The role of residual stress is critical for the lattice distortion of HAp deposited at physiological conditions of temperature and pH of human blood plasma. The ion concentration is crucial for the uniformity, crystallinity, and mechanical behaviour of the apatite.